Developmental trajectory of oligodendrocyte progenitor cells in the human brain revealed by single cell RNA sequencing. Issue 6 (20th January 2020) - Perlman, Kelly; Couturier, Charles P.; Yaqubi, Moein; Tanti, Arnaud; Cui, Qiao‐Ling; Pernin, Florian; Stratton, Jo Anne; Ragoussis, Jiannis; Healy, Luke; Petrecca, Kevin; Dudley, Roy; Srour, Myriam; et al.
Abstract: Characterizing the developmental trajectory of oligodendrocyte progenitor cells (OPC) is of great interest given the importance of these cells in the remyelination process. However, studies of human OPC development remain limited by the availability of whole cell samples and material that encompasses a wide age range, including time of peak myelination. In this study, we apply single cell RNA sequencing to viable whole cells across the age span and link transcriptomic signatures of oligodendrocyte‐lineage cells with stage‐specific functional properties. Cells were isolated from surgical tissue samples of second‐trimester fetal, 2‐year‐old pediatric, 13‐year‐old adolescent, and adult donors by mechanical and enzymatic digestion, followed by percoll gradient centrifugation. Gene expression was analyzed using droplet‐based RNA sequencing (10X Chromium). Louvain clustering analysis identified three distinct cellular subpopulations based on 5, 613 genes, comprised of an early OPC (e‐OPC) group, a late OPC group (l‐OPC), and a mature OL (MOL) group. Gene ontology terms enriched for e‐OPCs included cell cycle and development, for l‐OPCs included extracellular matrix and cell adhesion, and for MOLs included myelination and cytoskeleton. The e‐OPCs were mostly confined to the premyelinating fetal group, and the l‐OPCs were most highly represented in the pediatric age group, corresponding to the peak age of myelination. Cells expressing a signature characteristic of l‐OPCs were identified in the adult brain in situ using RNAScope. These findings highlight the transcriptomic variability in OL‐lineage cells before, during, and after peak myelination and contribute to identifying novel pathways required to achieve remyelination. Abstract : Human scRNA‐seq based OL‐lineage cell data was derived from immediately ex vivo surgically resected specimens covering a wide age range. Transcriptomic signatures were characterized across distinct stages of OL development, with links to specific biological processes.